2005
DOI: 10.1152/physiolgenomics.00020.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistance to fatigue and altered calcium handling properties of sarcalumenin knockout mice

Abstract: Sarcalumenin is a Ca2+-binding protein located in the sarcoplasmic reticulum of striated muscle cells, the physiological function of which has not been fully determined yet. Using sarcalumenin knockout (sar(-/-)) mice, we showed that sar ablation altered store-operated Ca2+ entry (SOCE) and enhanced muscle fatigue resistance. Sar(-/-) mice fatigued less with treadmill exercise, and intact isolated soleus and extensor digitorum longus muscles from sar(-/-) mice were more resistant to intermittent fatiguing stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
81
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 23 publications
5
81
3
Order By: Relevance
“…SAR knockout mice exhibit enhanced resistance to fatigue and altered Ca 2+ -handling properties (Zhao et al, 2005). SARdeficient fibres show diminished Ca 2+ -uptake into the SR lumen and enhanced store-operated Ca 2+ -entry appears to be a result of chronic adaptation from SAR ablation .…”
Section: Discussionmentioning
confidence: 99%
“…SAR knockout mice exhibit enhanced resistance to fatigue and altered Ca 2+ -handling properties (Zhao et al, 2005). SARdeficient fibres show diminished Ca 2+ -uptake into the SR lumen and enhanced store-operated Ca 2+ -entry appears to be a result of chronic adaptation from SAR ablation .…”
Section: Discussionmentioning
confidence: 99%
“…coupling, a finding that is also mirrored in aged skeletal muscles, which have an ϳ50% reduction in the protein content of MG29 (77,78). In contrast, improved muscle performance in an animal model where the MG29 level was up-regulated has been reported (79). Therefore, the up-regulation of Mg29 along with the up-regulation of other muscle performance genes helps explain the increased contractile performance of SOL muscles from cKO mice.…”
Section: Discussionmentioning
confidence: 93%
“…Sarcalumenin is a Ca 2+ -binding protein located in the sarcoplasmic reticulum of striated muscle cells. Its physiological function has not been fully determined, but some studies have shown that sarcalumenin affected store-operated Ca 2+ entry and enhanced muscle fatigue resistance in sarcalumenin knockout mice (Zhao et al, 2005;Yoshida et al, 2005). The large difference in the expression of calcium-transporting ATPase and sarcalumenin in colonies C and M also suggested that colony C engaged in stronger muscular movements when infected with Varroa mites.…”
Section: Discussionmentioning
confidence: 99%